2022
DOI: 10.1177/03000605221138461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoking on alveolar bone thickness and density in patients undergoing leveling and alignment of crowded lower anterior teeth: a controlled clinical trial

Abstract: Objective To evaluate the effect of cigarette smoking on the alveolar bone thickness and density in patients undergoing leveling and alignment of crowded lower anterior teeth. Methods This controlled clinical trial involved 17 smokers and 17 nonsmokers with mild to moderate crowding of the anterior mandibular teeth. Two cone-beam computed tomography images of the mandible were taken before and after treatment. The length of each tooth root was calculated in each T0 image, and the root was divided into three eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The total treatment time was 38 months, including the total orthodontic and prosthodontic rehabilitation. Slow tooth movement might be attributed to the patient's smoking habit 9,10,12 . Despite multiple reminders about the disadvantages of smoking on the rate of tooth movement and success rate of dental implants, our patient chose not to quit the habit resulting in a prolonged treatment time and possibly influencing the success rate of the dental implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total treatment time was 38 months, including the total orthodontic and prosthodontic rehabilitation. Slow tooth movement might be attributed to the patient's smoking habit 9,10,12 . Despite multiple reminders about the disadvantages of smoking on the rate of tooth movement and success rate of dental implants, our patient chose not to quit the habit resulting in a prolonged treatment time and possibly influencing the success rate of the dental implants.…”
Section: Discussionmentioning
confidence: 99%
“…An interdisciplinary approach is essential for establishing the proper diagnosis and treatment plan for patients having multidisciplinary problems combined with dental problems, 1 periodontal problems, 2,3 missing teeth, 4,5 mutilated dentition, 6–8 smoking, 9,10 temporomandibular joint (TMJ) disease, 11 medical problems, 2,12 and orthodontic malocclusion 1–7 . Multidisciplinary treatment includes restorative, 1,6,13 endodontic, 13 dental implants, 3,4,6,7,14–17 periodontal, 2,3,13,16 prosthetic, 1,3,4,7 oral medicine, 11,18 surgical, 1 orthodontic, 1–7 and medical intervention 2,12 …”
Section: Introductionmentioning
confidence: 99%
“…Ghadimi et al showed that nicotine reduces bone formation by stimulating the formation and differentiation of osteoclasts while inhibiting the activity of osteoblasts [21]. In a clinical trial involving patients undergoing orthodontic procedures, smokers experienced a 19.8% reduction in cortical bone thickness and a 23.5% decrease in cortical bone density, which damaged the alveolar bone [22]. A risk-prediction model for OP showed that alcohol consumption was a risk factor [23].…”
Section: Iof One-minute Op Risk Assessmentmentioning
confidence: 99%